Reassessing the Legal Validity of Non-Notarial Gifts Between Parents and Children Under Indonesian Law: A Doctrinal and Judicial Perspective - Yuningsih, Yuyun; Lisiani Prihatinah, Tri; Sulistyandari (Jurnal Hukum In Concreto, 2025)
Gifts (hibah) from parents to children are a common practice within family legal relations in Indonesia. However, the frequent execution of such gifts without notarial deeds raises serious concerns regarding their legal validity and the protection of other heirs' rights. This study reassesses the legal status of non-notarial gifts within the framework of Indonesian civil law and Islamic inheritance law. Employing a normative legal method through doctrinal and jurisprudential approaches, the research analyzes statutory provisions and judicial decisions to evaluate the enforceability and evidentiary strength of gifts made without authentic deeds. The findings reveal that non-notarial gifts generally fail to meet the formal legal requirements under Indonesian positive law, and are often declared invalid by courts, particularly when challenged by other heirs. Consequently, such gifts may infringe upon the legitime portie (compulsory inheritance share) and trigger intra-family inheritance disputes. This study asserts that legal formalities are not mere administrative procedures but serve as essential instruments to uphold legal certainty, balance competing interests, and achieve intergenerational justice. Accordingly, it recommends enhancing public legal literacy, expanding access to notarial services, and reforming regulatory frameworks to align customary practices with adequate legal protection.